2013
DOI: 10.1371/journal.pone.0057462
|View full text |Cite
|
Sign up to set email alerts
|

Delineating the Cytogenomic and Epigenomic Landscapes of Glioma Stem Cell Lines

Abstract: Glioblastoma multiforme (GBM), the most common and malignant type of glioma, is characterized by a poor prognosis and the lack of an effective treatment, which are due to a small sub-population of cells with stem-like properties, termed glioma stem cells (GSCs). The term “multiforme” describes the histological features of this tumor, that is, the cellular and morphological heterogeneity. At the molecular level multiple layers of alterations may reflect this heterogeneity providing together the driving force fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(58 citation statements)
references
References 84 publications
5
52
0
1
Order By: Relevance
“…Further studies have analyzed different types of genetic diversity within TICs and showed that glioblastoma TICs and non-TICs had abnormal karyotypes but reported that these karyotypes were clonal and that single cell clones were genetically homogeneous (12,14,3638). In contrast, we demonstrate that glioblastoma TICs have extensive sub-clonal karyotype heterogeneity and that single cell clones do not maintain a homogenous karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…Further studies have analyzed different types of genetic diversity within TICs and showed that glioblastoma TICs and non-TICs had abnormal karyotypes but reported that these karyotypes were clonal and that single cell clones were genetically homogeneous (12,14,3638). In contrast, we demonstrate that glioblastoma TICs have extensive sub-clonal karyotype heterogeneity and that single cell clones do not maintain a homogenous karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…GBM is heterogeneous in many ways, including appearance, genetic composition and the variety of mechanisms by which it evades therapy [21]. Extensive study of GBM has borne out the concept that within tumors, cells exist both in differentiated and undifferentiated, progenitor-like states [20].…”
Section: Glioma Stem Cell Biology and Its Role In Gbmmentioning
confidence: 99%
“…The seven GSC lines used in this study (GBM2, GBM7, GBM04, G144, G166, G179 and GliNS2) were isolated from patients affected by GBM (22,23) and, in 2013, our research group characterized their cytogenomic and epigenomic profiles (24). Cells were cultured in neural stem cell-specific medium, and their stem-like properties were periodically monitored, as previously described (22)(23)(24).…”
Section: Methodsmentioning
confidence: 99%
“…The seven GSC lines used in this study (GBM2, GBM7, GBM04, G144, G166, G179 and GliNS2) were isolated from patients affected by GBM (22,23) and, in 2013, our research group characterized their cytogenomic and epigenomic profiles (24). Cells were cultured in neural stem cell-specific medium, and their stem-like properties were periodically monitored, as previously described (22)(23)(24). Cells were cultured in an adherent culture condition using 10 µg/ml laminin (Invitrogen) in a proliferation permissive medium composed of Dulbecco's modified Eagle's medium (DMEM)/F-12 and Neurobasal 1:1 (Invitrogen), B-27 supplement without vitamin A (Invitrogen), 2 mM L-glutamine, 10 ng/ml recombinant human bFGF and 20 ng/ml recombinant human EGF (Miltenyi Biotec), 20 uI/ ml penicillin and 20 µg/ml streptomycin (Euroclone).…”
Section: Methodsmentioning
confidence: 99%